Genetic characterization of three recently discovered parvoviruses circulating in equines in China - Ou, JiaJun; Li, Jinghao; Wang, Xijie; Zhong, Lintao; Xu, Liang; Xie, Jinxin; Lu, Gang; Li, Shoujun (Frontiers in Veterinary Science, 2022)
The family Parvoviridae comprises many major viral pathogens that can infect humans and multiple other species, causing severe diseases. However, knowledge of parvoviruses that infect equids is limited. In the present study, we found that three equine parvoviruses (EqPVs), namely, equine parvovirus-hepatitis (EqPV-H), equine parvovirus-cerebrospinal fluid (EqPV-CSF) and equine copivirus (EqCoPV) cocirculated among horses in China. We examined the prevalence of these three EqPVs in 225 horse serum samples in China and found EqPV-H, EqPV-CSF and EqCoPV viremia in 7.6% (17/225), 2.7% (6/225) and 2.2% of samples (5/225), respectively. We also obtained the complete genomes of one EqPV-H strain, six EqPV-CSF strains and one EqCoPV strain. After phylogenetic analysis of the EqPVs, we found that EqPV-CSF and EqCoPV may have evolved from the same ancestor. The EqPV-CSF strains (E111 and A27) and EqCoPV strain (F124) were genetically similar to foreign strains, but the EqPV-CSF strains (B48, E96, C61 and F146) comprised unique clades. This study determined the prevalence of three EqPVs in Chinese horses and analyzed the genetic characteristics of EqPVs prevalent strains in Chinese horse herds. Our data provide a theoretical basis for follow-up research on the prevention and control of EqPVs.